1978
DOI: 10.2172/6417825
|View full text |Cite
|
Sign up to set email alerts
|

Energy level structure and transition probabilities in the spectra of the trivalent lanthanides in LaF₃

Abstract: The spectroscopic investigations of lanthanide doped LaF^ crystals and their theoretical interpretation reported here are the result of an extensive joint effort of the Argonne National Laboratory and The Johns Hopkins University over the last decade. It had its roots in similar studies at both laboratories of other crystal hosts, particularly LaCl 3> for which a summary is also given in an appendix to this report. This work was supported at Argonne by the United States Atomic Energy Commission and the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
527
0
16

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(564 citation statements)
references
References 0 publications
21
527
0
16
Order By: Relevance
“…The narrow peaks observed in the emission spectra are transitions between the excited 4 G 5/2 level and the different J-levels of the 6 H term. 96,97 The most intense transition is the 4 G 5/2 f 6 H 9/2 line at 648 nm. Just as in the case of the europium(III), it was found that the monitoring of the luminescence lifetime can be used to detect the clearing point of a samarium(III)-containing liquid crystal.…”
Section: Results and Dissussionmentioning
confidence: 99%
“…The narrow peaks observed in the emission spectra are transitions between the excited 4 G 5/2 level and the different J-levels of the 6 H term. 96,97 The most intense transition is the 4 G 5/2 f 6 H 9/2 line at 648 nm. Just as in the case of the europium(III), it was found that the monitoring of the luminescence lifetime can be used to detect the clearing point of a samarium(III)-containing liquid crystal.…”
Section: Results and Dissussionmentioning
confidence: 99%
“…The reduced matrix elements of U (λ) in Eq. 2 have been calculated, in the intermediate coupling scheme, for the whole series of the trivalent lanthanides 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic-dipole transitions give only a negligible contribution to the transition bands of Nd 3+ so that they are not taken into account [34,35]. The electric-dipole strength is given by…”
Section: Judd-ofelt Parameters and Emission Propertiesmentioning
confidence: 99%
“…The reduced matrix elements <\\U (t) \\> are almost insensitive to the environment and the values provided by Carnall et al have been used [35]. Intensity parameters Ω 2 , Ω 4 and Ω 6 , obtained by the leastsquares method, are shown in Table 4 and compared to those obtained for other silicate glasses in which the alkali and alkaline-earth oxide modifiers have been exchanged between Li + , Na + , K + and Mg 2+ and Ca 2+ respectively.…”
Section: Judd-ofelt Parameters and Emission Propertiesmentioning
confidence: 99%